Effects of Dietary Ramie Powder at Various Levels on the Production Performance, Serum Biochemical Indices, Antioxidative Capacity, and Intestinal Development of Laying Hens - Wang, Xin; Liu, Yang; Zhao, Hao-Han; Wu, Yong-Mei; Liu, Chun-Jie; Duan, Guang-Ying; Wang, Yan-Zhou; Liu, Tou-Ming; Huang, Peng; Li, Ying-Hui; Fan, Zhi-Yong; Qiu, Hua-Jiao; et al. (Frontiers in Physiology, 2022)
The purpose of this study was to investigate the effects of dietary ramie (0, 3, 6, 9%) on the production performance, antioxidative capacity, serum biochemical indices and intestinal development in laying hens. A total of 432 Lohmann commercial laying hens were randomly allotted to 1 of 4 dietary treatments and fed for 6 wk. The results showed that the inclusion of ramie had no negative effects on laying performance, and increased (quadratic, P<0.05) the laying rate with the highest value of laying rate in 6% ramie group. However, when ramie content in the diet up to 9%, it would affect the apparent metabolic energy of laying hens and the nutrient utilization rate of dry matter and organic matter. The content of serum highdensity lipoprotein (HDL-C) was increased (P<0.05) by ramie, while aspartate aminotransferase (AST) was decreased (P<0.05). Moreover, ramie could increase serum glutathione peroxidase (GSH-Px) activity (P<0.05) and liver total superoxide dismutase (SOD) activity (P<0.05). The addition of ramie increased (P<0.05) villus height of jejunum and villus height/crypt depth (V/C) of ileum. In conclusion, ramie in a diet not more than 9% may lower blood lipid, protect the liver and improve antioxidative capacity without any negative impacts on health or laying performance; meanwhile, it could beneficially promote intestinal mucosal structure which has a positive impact on intestine health.